Chaos, danger, and maternal parenting in families: Links with adolescent adjustment in low‐ and middle‐income countries. Issue 5 (30th May 2019) - Deater‐Deckard, Kirby; Godwin, Jennifer; Lansford, Jennifer E.; Tirado, Liliana Maria Uribe; Yotanyamaneewong, Saengduean; Alampay, Liane Peña; Al‐Hassan, Suha M.; Bacchini, Dario; Bornstein, Marc H.; Chang, Lei; Di Giunta, Laura; Dodge, Kenneth A.; et al.
Abstract: The current longitudinal study is the first comparative investigation across low‐ and middle‐income countries (LMICs) to test the hypothesis that harsher and less affectionate maternal parenting (child age 14 years, on average) statistically mediates the prediction from prior household chaos and neighborhood danger (at 13 years) to subsequent adolescent maladjustment (externalizing, internalizing, and school performance problems at 15 years). The sample included 511 urban families in six LMICs: China, Colombia, Jordan, Kenya, the Philippines, and Thailand. Multigroup structural equation modeling showed consistent associations between chaos, danger, affectionate and harsh parenting, and adolescent adjustment problems. There was some support for the hypothesis, with nearly all countries showing a modest indirect effect of maternal hostility (but not affection) for adolescent externalizing, internalizing, and scholastic problems. Results provide further evidence that chaotic home and dangerous neighborhood environments increase risk for adolescent maladjustment in LMIC contexts, via harsher maternal parenting. Abstract : This figure shows the significant direct and indirect pathways over three years of adolescence in six low‐ and middle‐income countries, linking chaos and neighborhood danger (13 years old), with harsher maternal parenting behaviors (14 years), then higher levels of externalizing problems (e.g. aggression, delinquency) (15 years). Similar effects were observed for internalizing problems (e.g. anxious/depressed, withdrawn) and academic problems. Results were largely consistent across countries.